Os registos de escrita precoce de crianças de 5-6 anos: evidência da evolução das conceções precoces sobre a linguagem escrita - Vieira da Silva, Maria Cristina (2023)
The paper aims to show how the records (Ostetto, 2017) concerning emerging literacy practices obtained in the context of supervised teaching practice, with children aged 5-6 years, allowed to collect evidence about the different stages in which children were, in terms of early conceptions about written language. Based on a sample of eight children aged five and six year-old, an interview guide was selected to evaluate early conceptions about written language, from which records of children’s written productions were collected, as well as a survey about the functionalities they attributed to reading and written language. The analysis of the collected data showed that the records of written productions were decisive to the categorization of children's conceptualizations about written language providing an opportunity for the trainee teacher to appropriate some aspects of emerging literacy, a particularly relevant dimension in terms of professional teacher training in Early Childhood Education (Gimeno, 1988).